2020
DOI: 10.3390/en13082034
|View full text |Cite
|
Sign up to set email alerts
|

Annual Energy Consumption Cut-Off with Cooling System Design Parameter Changes in Large Office Buildings

Abstract: A variety of greenhouse gas reduction scenarios have been proposed around the world to ensure sustainable developments and strengthen the global response to the climate change. To cope with this, it is urgently needed to reduce the amount of energy used for the heating, ventilating, air conditioning, and refrigerating (HVAC&R) systems in large buildings. This study discusses the reduction of cooling energy in large office buildings through the minimization of changes in components and equipment, such as he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The ISO standard (EN ISO 6946:2008) reported the key factor to indicate the thermal properties of the building is heat transfer (U) in which lower U-value indicates higher energy savings [30]. The U-value [31] and the energy transfer or heat flow (Q) [32] were calculated using Equations ( 1) and (2) [33,34]:…”
Section: Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISO standard (EN ISO 6946:2008) reported the key factor to indicate the thermal properties of the building is heat transfer (U) in which lower U-value indicates higher energy savings [30]. The U-value [31] and the energy transfer or heat flow (Q) [32] were calculated using Equations ( 1) and (2) [33,34]:…”
Section: Energy Consumptionmentioning
confidence: 99%
“…The design temperature outside and inside the house was specified by local guidelines as 46 • C and 24 • C, respectively. Moreover, the U-value of the floor and roof slabs were obtained from local standards and they were compared to ASHRAE (American society of heating, refrigerating and air-conditioning engineers) specifications based on perimeter to area ratio and thermal resistance values [33,34].…”
Section: Energy Consumptionmentioning
confidence: 99%
“…Because chillers account for 50% of the energy consumed by cooling systems [3], various studies have been conducted to reduce the energy of a chiller in heating, ventilation, and air conditioning (HVAC) systems. Ha et al (2020) analyzed the energy consumption according to temperature variation and chilled water outlet temperature of the main cooling period in order to increase the coefficient of performance (COP) of a chiller [4]. The results showed that energy savings of up to 12.4% were realized at a chiller water exit temperature of 7 • C and a temperature difference of 10 K. Thu et al (2017) analyzed the changes in the chiller COP and cooling capacity according to the increase in the temperature of chilled water for mechanical vapor compression (MVC) chillers [5].…”
Section: Introductionmentioning
confidence: 99%